Demographic and clinical characteristics of a paediatric low vision population in a low vision clinic in China. (4th May 2016) - Gao, Guohong; Yu, Manrong; Dai, Jinhui; Xue, Feng; Wang, Xiaoying; Zou, Leilei; Chen, Minjie; Ma, Fei
Abstract: Purpose: The aim was to describe the characteristics of the paediatric population attending the low vision clinic of the Eye and ENT Hospital, located in Shanghai, China. Methods: The clinical records of all the children attending the low vision clinic of Eye and ENT Hospital affiliated to Fudan University between January 1, 2009 and May 31, 2014 were retrospectively reviewed. The main data analysed were age, gender, education, visual demand, diagnosis, visual acuity and prescription of low vision aids. Results: Of the 162 patients, 104 (64.20 per cent) were male. The age range of the study population was three to 20 years, with a mean of 10.73 ± 5.08 years. There were 43.21 per cent with moderate visual impairment, 26.54 per cent had severe visual impairment and 19.75 per cent were blind. The leading causes of visual impairment were congenital cataract (21.61 per cent), optic atrophy (14.20 per cent), macular dystrophy (11.73 per cent), nystagmus (9.88 per cent) and congenital glaucoma (9.26 per cent). The most frequently prescribed low vision devices for distant and near vision were binocular telescopes (23.57 per cent) and stand magnifiers (22.93 per cent), respectively. Young age (up to six years, 37.93 per cent), high cost (24.14 per cent), cosmetic reasons (17.24 per cent) and inconvenience (13.79 per cent) were the main reasons that children or parents refused to accept useful low vision aids. Conclusions: Congenital and hereditary diseases constituted the major causes of low vision in the study population. Strategies that make good‐quality rehabilitation services available, affordable and accessible, especially in developing countries, will have the greatest impact on visual impairment. In China, both urban and rural, the coverage of low vision services should be strengthened.